1972
DOI: 10.1161/01.res.31.3.317
|View full text |Cite
|
Sign up to set email alerts
|

Protein Synthesis and Amino Acid Transport in the Isolated Rabbit Right Ventricular Papillary Muscle: EFFECT OF ISOMETRIC TENSION DEVELOPMENT

Abstract: To investigate the effects of isometric tension development on myocardial protein metabolism, 14 C-phenylalanine incorporation into protein was studied in the isolated rabbit right ventricular papillary muscle. Amino acid incorporation was linear for 6 hours in resting muscles and was totally inhibited by ICHM cycloheximide and ICHM puromycin. Phenylalanine incorporation into total protein was unaltered by 90 minutes of isometric tension development at peak tension at stimulation rates of 30, 50, or 100/min. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
2

Year Published

1977
1977
2004
2004

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(32 citation statements)
references
References 36 publications
4
26
2
Order By: Relevance
“…It has previously been shown that the increased rates of protein break-down after denervation (Goldberg, 1969;Goldspink, 1976) can be inhibited by direct electrical stimulation of isolated muscles . Although Goldberg et al (1975) found no change in protein synthesis of skeletal muscle after electrical stimulation in vitro, Peterson & Lesch (1972) observed an increased incorporation of amino acids into proteins of the papillary muscle of the heart after repeated stimulations. Also in keeping with the present study Hamosh, Lesch, Baron & Kaufman (1967) found increased rates of protein synthesis during work-induced hypertrophy of skeletal muscle.…”
Section: Discussionmentioning
confidence: 89%
“…It has previously been shown that the increased rates of protein break-down after denervation (Goldberg, 1969;Goldspink, 1976) can be inhibited by direct electrical stimulation of isolated muscles . Although Goldberg et al (1975) found no change in protein synthesis of skeletal muscle after electrical stimulation in vitro, Peterson & Lesch (1972) observed an increased incorporation of amino acids into proteins of the papillary muscle of the heart after repeated stimulations. Also in keeping with the present study Hamosh, Lesch, Baron & Kaufman (1967) found increased rates of protein synthesis during work-induced hypertrophy of skeletal muscle.…”
Section: Discussionmentioning
confidence: 89%
“…22 The amount of cardiac hypertrophy is the summation of changes in corresponding rates of myocardial protein synthesis and degradation. The synthesis of myocardial protein is not only affected by mechanical stress, 23,24 but also by Ang II. 24 On the basis of these findings, cardiac AM gene transcription is also enhanced by the stimulation of cardiac protein synthesis, such as that through mechanical stress and/or RAS, as a result of different loading conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Peterson was the first to report that stretch of quiescent papillary muscle accelerates protein synthesis. 3 It was subsequently shown that elevation of aortic pressure increases protein synthesis in beating-perfused hearts. 4 In addition, Cooper et al 5 reported that in aorta-constricted cats, papillary muscle whose tendon has been cut to release tension does not represent hypertrophy, whereas neighbouring uncut papillary muscle shows marked hypertrophy, and that cardiac hypertrophy is induced by pressure overload even under the denervation of ventricular adrenoceptors.…”
Section: Haemodynamic Overload and The Cardiac Renin-angiotensin Systemmentioning
confidence: 99%